2021
DOI: 10.1146/annurev-ento-072720-095043
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors and Interactions of Insects in Mid-Mesozoic Ecosystems of Northeastern China

Abstract: During the past 20 years, more than 1,600 species of well-preserved fossil insects, including members of over 270 families within 24 orders, have been described from the Middle Jurassic Yanliao Entomofauna and Early Cretaceous Jehol Entomofauna in Northeastern China. Diversified fossil insects not only document the origin, systematics, and early evolution of many lineages, but also reveal these lineages’ behaviors and interactions with coexisting plants, vertebrates, and other insects in their ecosystems. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 95 publications
0
28
0
Order By: Relevance
“… Archidermaptera were seemingly the most abundant form of earwigs during these epochs, with 28 species in 21 genera (Table 1 ), compared to only seven species in five genera of Eodermaptera . Numerous fossil insects and plants have been described from the Jiulongshan Formation (e.g., Ren et al 2010 ; Gao et al 2021 ), yet earwigs are comparatively rare, with only eight species reported from the locality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Archidermaptera were seemingly the most abundant form of earwigs during these epochs, with 28 species in 21 genera (Table 1 ), compared to only seven species in five genera of Eodermaptera . Numerous fossil insects and plants have been described from the Jiulongshan Formation (e.g., Ren et al 2010 ; Gao et al 2021 ), yet earwigs are comparatively rare, with only eight species reported from the locality.…”
Section: Discussionmentioning
confidence: 99%
“…Three specimens were collected from the Middle Jurassic Jiulongshan Formation at Daohugou Village, Ningcheng County, Inner Mongolia, northeastern China. The age of the fossil deposit is approximately 164–165 Ma ( Chen et al 2004 ; Ren et al 2010 ; Gao et al 2021 ; Yang et al 2021 ), within the Callovian stage of the later Middle Jurassic. The material is housed in the Key Lab of Insect Evolution and Environmental Changes, the College of Life Sciences, Capital Normal University, Beijing ( CNU ; Dong Ren, Curator).…”
Section: Methodsmentioning
confidence: 99%
“…This site is part of the famous Jehol Biota [12], belonging to the Yixian Formation stratigraphically, consisting mainly of lacustrine sediments intercalated with volcanoclastics [13][14][15]. Paleobotanical data from fossil spores, pollen, and plants indicate a rather warm and humid climate at that time [12,[16][17][18][19]. The age of the strata is regarded as Early Cretaceous (Hauterivian to Aptian in age) [15,20,21].…”
Section: Methodsmentioning
confidence: 99%
“…The non-marine Jurassic and Cretaceous deposits of northern China are rich and diverse in fossil insects (Wang et al 2012;Cai and Huang 2014;Fang et al 2020;Gao et al 2021;Yang et al 2021). In the Yanliao and Jehol biota, Prophalangopsidae are the most diverse and abundant Orthoptera with over thirty valid species, while the Haglidae have lower diversity and abundance.…”
Section: Introductionmentioning
confidence: 99%